Theory and Simulation of Linearized Force Coefficients for Active Magnetic Bearings with Multiple Magnetic Poles - Tianpeng Fan; Jinpeng Yu; Zhe Sun; Xingnan Liu; Xiaoshen Zhang; Jingjing Zhao; Xunshi Yan; Haoyu Zuo; Zhengang Shi (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Active magnetic bearing (AMB) is a kind of typical mechatronic product which is widely used due to its high performance. Since the electromagnetic force is strongly nonlinear, the force-displacement coefficient and the force-current coefficient need to be linearized in the process of controlling the AMB. This paper analyzes the three most common magnetic bearings and gives their linearized force formulas. Simulations show that the formulas have high precision. In addition, the source of errors is also analyzed in this paper.